School Of Architecture - AMLEH, AYMAN (My University, 2020)
School of architecture … This project was designed by Arch Ayman Amleh and directed by Dr HAsan Al – Qadi , Dr Khaled Qamheieh , and Arch Dua mallah This project is all about creating new generation of architects who’d be able to change the current architectural situation bu allowing them to have a whole different story throw their school life it enhance the challenging spirit they have and gives them the inspiration and courage it also allow them to have a great social life and circulation experience The project is located in Ramallah city al rihan hood beside the compose of the arab American university